Answer:
[tex]P_x = -2, P_y =4, P_z =-4[/tex]
[tex]Q_x = 3, P_y =1, P_z =0[/tex]
Replacing we got:
[tex] x = \frac{-2+3}{2}=\frac{1}{2}[/tex]
[tex] y= \frac{4+1}{2}=\frac{5}{2}[/tex]
[tex] z =\frac{-4+0}{2}=-2[/tex]
And then the midpoint would be:
[tex] M= (\frac{1}{2} , \frac{5}{2}, -2)[/tex]
Step-by-step explanation:
We have the following two points P(-2,4,-4) and Q(3,1,0) and the midpoint for this case is given by this:
[tex] x= \frac{P_x +Q_x}{2}[/tex]
[tex] y= \frac{P_y +Q_y}{2}[/tex]
[tex] z= \frac{P_z +Q_z}{2}[/tex]
And from the problem given we have:
[tex]P_x = -2, P_y =4, P_z =-4[/tex]
[tex]Q_x = 3, P_y =1, P_z =0[/tex]
Replacing we got:
[tex] x = \frac{-2+3}{2}=\frac{1}{2}[/tex]
[tex] y= \frac{4+1}{2}=\frac{5}{2}[/tex]
[tex] z =\frac{-4+0}{2}=-2[/tex]
And then the midpoint would be:
[tex] M= (\frac{1}{2} , \frac{5}{2}, -2)[/tex]